Gait-Based Quadruped Robot Planar Hopping Control with Energy Planning. (9th February 2016) - Chai, Hui; Rong, Xuewen; Tang, Xingpeng; Li, Yibin
To improve the mobility of the quadruped robot, a planar hopping control approach is proposed based on trotting gait. With the proposed approach, three joints of the stance legs are active and the fourth leg is passive. A planar kinematic model of the supporting phase is built and the calculated positions and posture of the torso are used as feedback for motion control. The forces and torque acting at the CoM of the robot torso in the plane are fully controllable and decoupled with the control approach based on a virtual model. The planar motions on three axes are controlled independently. For the hopping control, the total energy in a hopping cycle on the vertical direction is planned according to the desired hopping height of the torso's CoM and the virtual vertical stiffness of the torso is generated using the elastic potential energy of the virtual model. We verify the approach and its robustness using simulation experiments and show the results at the end of this paper.